Nasal Tip Cutaneous Metastasis of Hepatocellular Carcinoma: A Case Report - Li S; Cai X; Yu K; Pan W (Dove Medical Press, 2023)
Songting Li,1,2 Xiaolan Cai,3 Keyao Yu,1,2 Weihua Pan1,2 1Department of Dermatology, Second Affiliated Hospital of Naval Medical University, Shanghai, People's Republic of China; 2Shanghai Key Laboratory of Molecular Medical Mycology, Shanghai, People's Republic of China; 3Department of Otorhinolaryngology, Qilu Hospital of Shandong University, Jinan, People's Republic of ChinaCorrespondence: Weihua Pan, Department of Dermatology, Second Affiliated Hospital of Naval Medical University, Shanghai, People's Republic of China, Tel +86-2188485495, Email panweihua9@sina.comBackground: Cutaneous metastasis is rare in clinical practice, especially that from primary hepatocellular carcinoma (HCC), which is even rarer.Case Presentation: This report describes a male patient with HCC with cutaneous metastases to the nasal tip. The patient developed a raised nodule at the nasal tip 5 years after surgery for HCC, with surface ulceration and crusting and no obvious symptoms. Abdominal computed tomography (CT) showed an obvious mass in the liver. The skin lesions on the nasal tip were confirmed to be cutaneous metastasis of HCC by histopathological and immunohistochemical examinations.Conclusion: The incidence of cutaneous metastasis of HCC is extremely low, and nasal tip cutaneous metastasis of HCC has no specific clinical manifestations; therefore, it needs to be distinguished from rosacea rhinophyma, fungal and atypical mycobacterial infections, tumours of vascular origin, and tumours of skin appendages that occur in the nasal tip and is prone to misdiagnosis and missed diagnosis, thus requiring clinical dermatologists and otolaryngologists to be aware of such metastasis.Keywords: primary, hepatocellular carcinoma, metastatic cancer, skin, nasal tip